Study of teaching practices for the development of pre-reading skills at the Preschool level in Costa Rica-California, USA - Badilla Zamora, Isabel (2023)
This writing is based on a joint investigation between staff members from Universidad Nacional of Costa Rica and faculty researchers from universities of California, USA: Redlands,  California State University San Marcos and National University that is carried out during 2020 and 2021, which aims to know the teaching practices at the preschool level related to the development of pre-reading skills in both contexts. As a result of the interviews applied to thirty teachers, fifteen from each country, teaching practices are identified: similarities and particularities, in addition, the evaluative strategies used to assess pre-reading skills in preschool children are determined, as well as the challenges that face the teachers of each country. Finally, the interest of promoting opportunities for collaboration and learning between colleagues of both nationalities is established. In conclusion, teaching practices with the intention of developing pre-reading skills coincide in safeguarding and considering the characteristics of the age group. In addition, their practices include the use of printed material, games, and art, among others, as vehicles to integrate children into the literate world in the classroom. Likewise, the need and challenge of considering the context is considered when designing meaningful strategies and promoting real situations of childhood in the classroom such as conversations and dramatizations for the development of oral language and vocabulary.